Sequential release of cytokines, lipid mediators and nitric oxide in experimental colitis - A. P. M. van Dijk; Z. J. Keuskamp; J. H. P. Wilson; F. J. Zijlstra (Mediators of Inflammation)
The object of this study was to establish whether different pro- and anti-inflammatory mediators were formed in colonic tissue from experimental colitis depending on the course of the disease. Concentrations of mediators of inflammation were examined in colonic tissue in dextran induced colitis in mice. Initial inflammation was produced by 5 days treatment of 10% dextran sodium sulfate (DSS) in drinking water, followed by a further 9 day period of 2% DSS in an attempt to produce a milder chronic inflammation. The degree of inflammation was scored by a standardized macroscopic and histological examination. Initially, a 60% maximum inflammation score was observed at day 4. At this time inflammation was associated with the release of interleukin-lβ (IL-1β) and tumour necrosis factor-α (TNFα), whereas both prostaglandins 6kPGF1α and PGE2 and nitric oxide (NO) markedly decreased. Then a 25% inflammation score was reached which coincided with an increased production of platelet-activating factor (PAF). No significant changes were observed in leukotriene B4 and C4 formation. In conclusion, pro-inflammatory cytokines IL-1β and TNFα are considered to be primary mediators, whereas PAF, eicosanoids and NO may reflect secondary mediators in experimental colitis.